DESCRIPTION OF MATHEMATICAL LITERATION ELEMENTARY SCHOOL STUDENTS IN COLLABORATIVE LEARNING SETTINGS (Elementary Education Study Program School of Postgraduate Studies Universitas Pendidikan Indonesia in collaboration with UPI PRESS, 2018)
The purpose of this research is (1) to see the extent to which the mastery of mathematics elementary school students literacy country 015877 (2) look at the impact of collaborative learning against the ability of mathematical literacy elementary school students of the country 015877. This type of research using qualitative approach with data analysis using phenomenological descriptive. The sample of this research is the whole grade VI SDN 015877 Fifty which amounted to 28 students. Research findings demonstrating that the ability of mathematical literacy students rise seen from the average literacy test answers results' students who obtain a score above average as many as 21 students. and also the ability of other students showed improvement as the ability and proficiency in verbal argues rise after applied to collaborative learning. This is certainly be added value and also as an alternative solution for educators to address challenges of 21st century learning.